CONSTRUCTING COMPLIMENT IN ENGLISH AND BAHASA INDONESIA : A COMPARATIVE STUDY - Syaiful Akhyar (Balai Bahasa Nusa Tenggara Barat, 2015)
Compliment defined as a form of appreciation, entertainment, manifesting of satisfaction, and the way of encouragement to increase the learning motivation. It identifies that the form of compliment take some varieties of patterns. In Bahasa Indonesia, using metaphor seems to be one of the alternatives forms of composing compliment. It is also used by any different profession of humankind, from personal to interpersonal relationship, from ordinary people to the top politicians, in the formal and informal institution. In teaching and learning activity, teacher proposes compliment as the essential topic that must be acquired by the students. The acquisition of compliment can be taught by numerous strategies and techniques. It depends on the situation and school environment. The knowledge of linguistic expressions and sociolinguistics rules of the relevance topic should be put as the top consideration.